The role of gut microbiota imbalance in preeclampsia pathogenesis: insights into FMO3-mediated inflammatory mechanisms - Xu, Xia; Zhang, Ying; Zu, Yizheng; Xu, Yanhong; Liao, Tingting; Li, Xiuli; Yan, Jianying (Frontiers in Microbiology, 2025)
BackgroundPreeclampsia (PE) is a severe pregnancy complication linked to systemic inflammation and metabolic dysregulation. Emerging evidence suggests gut microbiota imbalance may contribute to PE pathogenesis, but the underlying mechanisms remain unclear. This study investigated whether gut dysbiosis triggers PE through flavin-containing monooxygenase 3 (FMO3)-mediated inflammatory pathways.MethodsWe transplanted fecal microbiota from PE rats, healthy pregnant (HP) rats, and non-pregnant (NP) rats into antibiotic-treated dysbiotic rats, with a control group receiving normal saline (CON). Additionally, FMO3 expression was inhibited using FMO3-RNAi in parallel groups. We measured blood pressure, urine protein, FMO3 protein and mRNA expression, inflammatory markers, liver and kidney function, embryo resorption rate, and fetal weight. Gut microbiota composition was analyzed by 16S rRNA gene sequencing. The impact of interleukin-8 (IL-8) on trophoblast cell function was assessed using cell counting kit-8 (CCK-8), transwell invasion, and tube formation assays.ResultsRats receiving PE fecal microbiota transplantation (FMT) exhibited a gradual rise in blood pressure post-pregnancy, varying degrees of liver and kidney damage, markedly elevated serum inflammatory cytokines, higher fetal resorption rates, and reduced placental weights. FMO3 protein and mRNA expressions were significantly higher in the PE-FMT group. FMO3 knockdown partially improved these perinatal outcomes. Antibiotic treatment significantly decreased gut microbiota alpha and beta diversity. At the genus level, the PE-FMO3-RNAi group showed increased Escherichia-Shigella and decreased Lactobacillus compared to the PE-CON-RNAi group. In cell experiments, elevated IL-8 levels decreased the viability and invasiveness of HTR-8/SVneo cells and diminished the angiogenic potential of human umbilical vein endothelial cells (HUVECs).ConclusionA disruption of gut microbiota could result in PE through the FMO3-driven inflammatory response, and targeting FMO3 may prove valuable in treating PE.